Lean Management concept in hospital management – possibilities and limitations - Brajer-Marczak, Renata; Wiendlocha, Andrzej (Management Sciences, 2018)
With reference to the current situation of national public hospitals, the article presents the possibility to implement the Lean Management concept in hospital management. Numerous common features connecting the management of commercial entities with the management of healthcare institutions are indicated. It has been stated that the management of contemporary organizations, regardless of the type of conducted operations, needs to focus on customer/patient satisfaction, financial liquidity and high quality. The purpose of the article is to assess the possibility to implement the Lean Management concept in hospitals. In particular, an attempt was made on the basis of a pilot survey to assess the introduction of the above concept in two selected hospitals. Critical analysis of the literature on the subject, the analysis of research results of other authors, casual interview, observation of practice as well as a survey based on the prepared questionnaire were used to achieve the purpose
Management Sciences, 2018, vol. 23, no. 1, s. 4-12
Keywords: lean management; Lean Health Care; process improvement; doskonalenie procesów